Marginal bone loss around crestal or subcrestal dental implants: prospective clinical study - Sargolzaie, Naser; Zarch, Hosein Hoseini; Arab, Hamidreza; Koohestani, Tahereh; Ramandi, Mahdiye Fasihi (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2022)
The stability of crestal bone has been reported as a major factor in the success of dental implants. Implants can be placed in an equicrestal (crestal) or subcrestal position. The aim of this study was to evaluate the effect of implant depth placement on marginal bone loss.ObjectivesThe stability of crestal bone has been reported as a major factor in the success of dental implants. Implants can be placed in an equicrestal (crestal) or subcrestal position. The aim of this study was to evaluate the effect of implant depth placement on marginal bone loss.The study was created in a split-mouth design. Immediately after implant surgery, digital parallel radiographs were prepared and levels of bone were measured where marginal bone loss and bone level changes occurred. These measurements were repeated at 3-month and 6-month follow-up periods.Materials and MethodsThe study was created in a split-mouth design. Immediately after implant surgery, digital parallel radiographs were prepared and levels of bone were measured where marginal bone loss and bone level changes occurred. These measurements were repeated at 3-month and 6-month follow-up periods.In this interventional study, 49 implants were evaluated in 18 patients. Primary bone height was not significant between the intervention and control groups in both mesial and distal aspects at 3 months and 6 months from the baseline. The mean marginal bone loss on the mesial side was 1.03 mm in the subcrestal group and 0.83 mm in the crestal group. In addition, mean marginal bone loss on the distal side was 0.88 mm and 0.81 mm in the subcrestal and crestal groups, respectively. Marginal bone loss was not significantly different between sexes, the maxilla or mandible, and in the anterior or posterior regions as well as between different lengths and diameters of implants.ResultsIn this interventional study, 49 implants were evaluated in 18 patients. Primary bone height was not significant between the intervention and control groups in both mesial and distal aspects at 3 months and 6 months from the baseline. The mean marginal bone loss on the mesial side was 1.03 mm in the subcrestal group and 0.83 mm in the crestal group. In addition, mean marginal bone loss on the distal side was 0.88 mm and 0.81 mm in the subcrestal and crestal groups, respectively. Marginal bone loss was not significantly different between sexes, the maxilla or mandible, and in the anterior or posterior regions as well as between different lengths and diameters of implants.Based on the results of this study, there was no significant difference in terms of marginal bone loss between crestal and subcrestal implants.ConclusionBased on the results of this study, there was no significant difference in terms of marginal bone loss between crestal and subcrestal implants.